Transformasi Generasi Muda Katolik: Liturgi sebagai Landasan Kaderisasi Orang Muda Katolik Stasi Sta. Renha Rosari Trans-Biduk, Sekatak, Kalimantan Utara - Caroline Resthy Wardhani Halawa; Angelika Bule Tawa (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This article discusses the transformation of young Catholics (OMK) through liturgy as a foundation for regeneration at Sta. Renha Rosari Trans-Biduk, North Kalimantan. The research focuses on the lack of understanding and involvement of OMK in liturgical practices, which poses a challenge for the church in increasing their participation. Through an inclusive approach and proper training, it is hoped that OMK can play an active role in the liturgy and strengthen their faith. The method used utilizes the ten steps of pastoral work. The results showed that despite barriers such as busyness and lack of confidence, with consistent coaching, the involvement of OMK in the liturgy can be increased.